2010
DOI: 10.1007/s10880-010-9198-z
|View full text |Cite
|
Sign up to set email alerts
|

Repression and Coping Styles in Asthmatic Patients

Abstract: The objectives of this study were to (a) determine prevalence of the dispositional repressive coping style as well as other situational coping styles in a sample of asthmatic patients and (b) to analyze the capacity of these styles to predict subsequent morbidity (emergency room visits or hospitalizations due to asthma) during a 12-month follow-up. A sample of 75 adult asthmatic patients was selected and information about sociodemographics, asthma severity, and patient's perception of illness severity was coll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 35 publications
2
13
0
Order By: Relevance
“…Accurate perception of symptoms is a crucial factor for correct self‐management in food allergy. In asthma, the use of emotion‐focused coping strategies seems to be related to a worse perception of physical status, and in particular, denial could promote a poor clinical course in asthma . Denial has also been found to be prevalent among a subgroup of food‐allergic children and teens, sometimes referred to as ‘minimization’ , giving rise to risk‐taking behaviours, such as not carrying an auto‐injector, not informing food venues, and not telling friends about food allergy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Accurate perception of symptoms is a crucial factor for correct self‐management in food allergy. In asthma, the use of emotion‐focused coping strategies seems to be related to a worse perception of physical status, and in particular, denial could promote a poor clinical course in asthma . Denial has also been found to be prevalent among a subgroup of food‐allergic children and teens, sometimes referred to as ‘minimization’ , giving rise to risk‐taking behaviours, such as not carrying an auto‐injector, not informing food venues, and not telling friends about food allergy.…”
Section: Discussionmentioning
confidence: 99%
“…Alexithymic patients tend not to adopt nuances in describing and discriminating feelings. They are more likely to express themselves in terms of bodily symptoms, providing excessive details of their health condition, behaviours and daily events , which can be interpreted as valid attempts to describe personal experience via symptoms or practical details. Understanding that a patient ‘cannot’, rather than ‘will not’, identify, distinguish and verbally express emotions, can improve patient–clinician communication and allow the clinician to select interventions that are appropriate and targeted specifically to that patient .…”
Section: Discussionmentioning
confidence: 99%
“…Given the limited research in these areas, it is hard to compare findings to previous literature. A few works have commented on the negative aspect of denial coping style, but most of these studies looked at its adverse consequence on mental health or its impact on recovery from health challenges (Gonzalez-Freire, Vazquez-Rodriguez, Marcos-Velazquez, & de la Cuesta, 2010;Goossens, Knoppert-van der Klein, & van Achterberg, 2008;Parikh et al, 2007). In a study among people recently diagnosed with diabetes, denial of the disease during the first 5 years was associated with poor glycemic control (Garay-Sevilla, Malacara, Gutiérrez-Roa, & González, 1999).…”
Section: R E S E a R C Hmentioning
confidence: 99%
“…These studies found that the use of defensive coping was significantly related to poorer HRQOL 40 and significantly higher rates of emergency department visits over a period of 12 months. 41 In contrast to this, another study found that defensive coping was associated with marginally better physical HRQOL. 42 Thus, defensive coping may act as a buffer against the harsh reality of the illness and its consequences, and provide short-term relief from the distress caused by having a chronic illness, for example, COPD.…”
Section: Hrqol-related Breathlessnessmentioning
confidence: 85%